The Effect of Work Demands, Workload and Transformational Leadership Style on Intention to Stay Mediated by Job Satisfaction in HR Managers of Automotive Companies in Bekasi Regency - Kusuma Praja, Adi Winata; Setyaningrum, Retno Purwani; Rezeki, Fitri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Based on the results of the study, Job Demand and Workload have a significant influence on Intention to Stay and Job Satisfaction, while Transformational Leadership does not show a significant influence. Job Satisfaction was also proven to mediate the relationship between Job Demand and Workload and Intention to Stay, but did not mediate the relationship between Transformational Leadership and Intention to Stay. These results show that job load and demands, as well as job satisfaction, play an important role in retaining employees, whereas transformational leadership does not exert a significant direct influence. This indicates the need to focus on workload management and job demands as well as increasing job satisfaction to retain employees.